1999
DOI: 10.1038/sj.bmt.1701905
|View full text |Cite
|
Sign up to set email alerts
|

Long-term liver function of recipients with hepatitis G virus infection after bone marrow transplantation

Abstract: Summary:To clarify the role of hepatitis G virus (HGV) infection in liver dysfunction following allogeneic BMT, we examined cryopreserved serum samples from 33 patients who had a history of blood transfusions before BMT and whose serum samples had been stored periodically, before BMT, on day 100, and thereafter for the presence of HGV-RNA and hepatitis C virus (HCV)-RNA by reverse transcription polymerase chain reaction. Nineteen patients (58%) out of 33 were positive for HGV-RNA before BMT and 10 for HCV-RNA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…5 Other papers analyze the results of serological tests in BMT and immunocompromised patients. 10,15,[17][18][19][20][21][22][23] Toma´s et al 23 found in a retrospective study of 61 BMT patients who had hepatic pathology, 29 patients with chronic hepatitis C of whom seven constantly tested anti-HCV negative but PCR positive. The Seattle group recommends hepatitis C testing, including viral RNA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…5 Other papers analyze the results of serological tests in BMT and immunocompromised patients. 10,15,[17][18][19][20][21][22][23] Toma´s et al 23 found in a retrospective study of 61 BMT patients who had hepatic pathology, 29 patients with chronic hepatitis C of whom seven constantly tested anti-HCV negative but PCR positive. The Seattle group recommends hepatitis C testing, including viral RNA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…34 The prevalence of HCV infection in patients with B-cell non-Hodgkin lymphoma and other lymphoproliferative disorders is between 8% and 32% and presents a significant management concern in these patients, 35 especially given the rare cases of liver failure that have been reported. 36,37 However, the reality is that hepatic dysfunction, clinical hepatitis flares, and fulminant hepatic failure are very uncommon events in HCV-infected patients who receive chemotherapy when compared to HBV-infected patients.…”
Section: Natural Historymentioning
confidence: 99%
“…Reverse seroconversion of HBV is not a rare complication in autologous HSCT, 43 and in allogeneic HSCT recipients the risk seems to be higher during the tapering of the immunosuppressive therapy. 42 Moreover, in this setting, fulminant hepatitis due to HCV 44,45 or HBV 46 has been described. Therefore, even if infection with hepatotropic viruses does not represent a major contraindication for HSCT, 47 a careful follow-up is recommendable, especially during immunosuppression tapering.…”
Section: Hepatitis Viruses In Autologous and Allogeneic Hsctmentioning
confidence: 99%
“…48 Finally, as regards infections due to 'other' hepatitis viruses, no data are available on HAV acute hepatitis after HSCT, while infection with HGV has been reported in HSCT recipients. [49][50][51] The data available in the pediatric population do not support any pathogenic role after either chemotherapy 52 or HSCT. 41 …”
Section: Hepatitis Viruses In Autologous and Allogeneic Hsctmentioning
confidence: 99%